A (i)materialidade da cultura italiana no município de Serafina Corrêa/RS: as relações culturais rurbanas - Stedile Neto, Ricardo (2019)
Cultural Geography has been the focus of geographers’ attention being highlighted as a reflective theme that explains the diversity of groups. The fact that cultural studies integrate the way of life into the space helps the understanding of different forms of its occupation and reorganization. The culture is responsible for the orientation of the actions of a particular social group, because it consists of a set of beliefs and values, in which are intrinsic to their essence. In Brazil, the research on Cultural Geography is deepening, mainly with the studies of migratory processes from the 19th century. Coming from Europe, immigrants, mostly Germans and Italians, were reterritorializing the state of Rio Grande do Sul and organizing it according to their cultural codes and the availability of natural resources discovered, forming diverse cultural landscapes. The Italian immigration to the state of Rio Grande do Sul officially began in the 1870s, and the mores that characterize many cities of the southern state to the present days were brought by Italian settlers. In this sense, the research has as central problem to analyze the (im)materiality of the culture in the socio-spatial dynamics of Serafina Corrêa. The main goal is to analyze the (im)materiality of the Italian culture in Serafina Corrêa, understanding the cultural relations prevailing in the rurban. Specifically, it was sought to: a) Identify how the Italian cultural (im)materiality is inserted in the current city scenario; b) Understand the sociospatial and economic dynamics that occurred in the spatial clipping under study and which impacts it has generated in the local culture; and c) Analyze the local public actions with the intention of preserving the culture in the present time. Methodologically, the research listed two methods of research, the phenomenological and the dialectical, because it was considered necessary to make a relation between the two methods to satisfactorily meet the proposed objectives. Afterward, the research was divided into 5 stages. In the first stage, we worked with the consolidation of the theme and the definition of the problem, the objective and, the scientific methods of the work. The second stage of the research consisted of data collection in secondary sources. The third step was the moment in which a research instrument was elaborated and used in the field work to search the information in loco, which consisted of questionnaires. The fourth stage of the research consisted of fieldwork, which was carried out in different periods. At the last step was done the analysis and interpretation of the results. Through the elaboration of this research, it was concluded that the Italian culture is still quite present in the rurban relations of the city, nevertheless, the new socio-spatial dynamics in the territorial unit impacted on these relations. Orality, religiosity and gastronomy stand out among the cultural codes present in the city. It is important to emphasize that the territorial unit has a great tourism potential based on the cultural bias.